Professional activity during studies by physiotherapy students of Master’s Degree course of university-level schools in Poland - Gotlib, Joanna; Szybińska, Małgorzata; Starczyńska, Małgorzata; Soboń, Jacek; Prokopowicz, Katarzyna; Nowotny-Czupryna, Olga; Majcher, Piotr; Lewandowski, Jacek; Plewa, Michał; Kułak, Wojciech; Hansdorfer-Korzon, Rita; Grzegorczyk, Joanna; et al. (Polish Journal of Public Health, 2013)
Introduction. In Poland, graduation from a Bachelor’s degree course with a Bachelor’s degree in Physiotherapy makes it possible to take on employment as a physiotherapist. However, a majority of students continues their education on a Master’s degree course and simultaneously works either as a physiotherapist or in another profession. We differ in this from other European countries.Aim. The aim of the study was to analyse the issue of taking on professional activity by second-year Physiotherapy students of a Master’s degree course of university-level schools of different educational profiles, i.e.: medical universities (PM), universities of physical education (PWF), and other schools (IP).Material and methods. The study enrolled 1942 second-year students of a Master’s degree course of 17 university-level schools A mean questionnaire return rate was: 53%. Women constituted 77% of the study participants, the mean age was 21 years. As many as 736 (45%) of the study participants started a Master’s degree course at the same university-level school at which they had graduated from a Bachelor’s degree course. The approval of the Ethical Review Board of Warsaw Medical University was not necessary to conduct the voluntary and anonymous questionnaire study. Statistical analysis: STATISTICA 10.0 (licensed to Warsaw Medical University), non-parametric statistical tests: Chi-square, Kruskall-Wallis, and Mann-Whitney U, p